Treatment with hypoxia‐mimetics protects cultured rat Schwann cells against oxidative stress‐induced cell death. Issue 9 (21st May 2021) - David, Brian T.; Curtin, Jessica J.; Brown, Jennifer L.; Coutts, David J. C.; Boles, Nathan C.; Hill, Caitlin E.
Abstract: Schwann cell (SC) grafts promote axon regeneration in the injured spinal cord, but transplant efficacy is diminished by a high death rate in the first 2–3 days postimplantation. Both hypoxic preconditioning and pharmacological induction of the cellular hypoxic response can drive cellular adaptations and improve transplant survival in a number of disease/injury models. Hypoxia‐inducible factor 1 alpha (HIF‐1α), a regulator of the cellular response to hypoxia, is implicated in preconditioning‐associated protection. HIF‐1α cellular levels are regulated by the HIF‐prolyl hydroxylases (HIF‐PHDs). Pharmacological inhibition of the HIF‐PHDs mimics hypoxic preconditioning and provides a method to induce adaptive hypoxic responses without direct exposure to hypoxia. In this study, we show that hypoxia‐mimetics, deferoxamine (DFO) and adaptaquin (AQ), enhance HIF‐1α stability and HIF‐1α target gene expression. Expression profiling of hypoxia‐related genes demonstrates that HIF‐dependent and HIF‐independent expression changes occur. Analyses of transcription factor binding sites identify several candidate transcriptional co‐regulators that vary in SCs along with HIF‐1α. Using an in vitro model system, we show that hypoxia‐mimetics are potent blockers of oxidative stress‐induced death in SCs. In contrast, traditional hypoxic preconditioning was not protective. The robust protection induced by pharmacological preconditioning, particularly with DFO, indicates that pharmacological induction of hypoxic adaptations could be useful for promoting transplanted SC survival. These agents may also be more broadly useful for protecting SCs, as oxidative stress is a major pathway that drives cellular damage in the context of neurological injury and disease, including demyelinating diseases and peripheral neuropathies. Main Points: HIF‐PHD inhibitors, DFO or AQ, stimulate HIF‐dependent and ‐independent transcriptional changes in SCs that mimic hypoxic preconditioning. Pharmacological, but not hypoxic, preconditioning potently blocks oxidative stress‐induced death in SCs.